Operational Audit Analysis In Credit Policy - Wildayanti Hidayah; Maman Nurochman; Tita Kartika (LPPM Universitas Sebelas April, 2021)
The purpose this research are (1) to determine wether operational audit of credit wisdom by Kredit Plus Sumedang has been in accordance with the regulation of Indonesia Central Bank No. 1/6/PBI/1999, and (2) to examine wether the wisdom of credit at Kredit Plus Sumedang in compliance with the guideline setting up by Kredit Plus Sumedang is related with the credit approval procedure. This research is a case study. Data was analysed by qualitative descriptive analysis. The data was primary data vthat was collected though interview with the employee of analisys credit. The results showed that the implementation of operational audit of credit wisdom at Kredit Plus Sumedang has been in accordance with the regulation of Indonesia Cental Bank No. 1/6/PBI/1999. The implementation of operational audit starts from of preparation of the audit, preparation of the audit programs, audit of assignment, reporting of audit results and follow up to the result of the audit conducted by the internal audit of Kredit Plus Sumedang are in accordance with applicable regulation of Indonesia Central Bank No.1/6/PBI/1999. Furthermore, it has been proven that the credit wisdom in Kredit Plus Sumedang Office which refers to the principles of credit 5C (Character,capacity,capital, collateral, condition), 5P (Purpose, payment, party, profitability, protection) and 3R (Return, repayment, risk bearing ability) has been implemented as it should and was in compliance with the guideline that have been set by Kredit Plus Sumedang.